FORMULATION AND EVALUATION OF ITRACONAZOLE NIOSOMAL GEL - Kumar, Ashish; Dua, J.S (Asian Journal of Pharmaceutical Research and Development, 2018)
The preparation of niosomes. The main objective of the study was to enhance the antifungal activity of the formulation. Itraconazole is a broad spectrum Imidazole derivative useful in the treatment of superfacial and systemic fungal infection. Various surfactants used were span 40 and span 60. Niosomes were prepared by using Rotary Vaccum evaporation method. Niosomes were prepared using different ratio of drug: surfactant: cholesterol (1:1:1, 1:2:1, 1:3:1).Evaluation of the Niosomal gel was done by determination of drug content 52.81-56.12, Entrapment Efficiency 42.20-45.20,Niosomal gel was prepared using Carbopol 940 (1.5%), Glycerol (10%), Triethanolamine (q.s.) and distilled water up to 15ml. Viscosity was determined by Brookfield programmable ultra-viscometer and the ranges 8173 centipoise. The drug content of the Itraconazole niosomal gel was determined at 262 nm against blank by using UV/visible spectrophotometer and found to be 56.12%. The percentage of drug entrapment in niosomal gel was calculated to be 45.20% .The in-vitro drug release study was carried out using phosphate buffer saline pH 7.4 and was found to be 41.18 ± 1.53% for 12 hours. It can be concluded that the gel formulation containing niosomes loaded with Itraconazole showed prolonged action than formulation containing Itraconazole in non-niosomal form and it can be developed successfully to improve the anti-fungal activity.